An association study on PSCA rs2294008 polymorphism and gastric cancer: A meta-analysis - Li, HangLong; Zhao, Qiang; Si, ShuHan; Wu, DongKai (Frontiers in Gastroenterology, 2022)
Studies have confirmed that prostate stem cell antigen (PSCA) rs2294008 C>T polymorphism is related to gastric cancer susceptibility, but some studies have reached the opposite conclusion. In this meta-analysis, we attempted to clear up these differences and explore the relationship between the different factors that influence susceptibility to gastric cancer. Studies with publication dates that preceded 16 April 2022 were selected from PubMed, Springer, EMBASE, and Web of Science, and the relationship between risk models and gastric cancer was analyzed by odds ratios (ORs) and 95% confidence intervals. Consequently, it was confirmed that PSCA rs2294008 polymorphism leads to an increased risk of gastric cancer. Subgroup analysis found that individuals with diffuse gastric cancer, non-cardia gastric cancer, Helicobacter pylori (HP)-positive or who are from the white or Asian population faced an increased susceptibility to gastric cancer. Those from the white populations faced significantly higher risks than Asians, and the association of PSCA with gastric cancer could be significantly increased by genome-wide association analysis. However, the conclusion that smoking reduces susceptibility to gastric cancer appears to be abnormal. Further prospective investigations that involve smoking and have a larger sample size are required.